(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The article analyzes the technical capabilities of carding machines at spinning mills and the properties of card sliver obtained at the enterprise. Conclusions are drawn by comparing the opportunities for reducing the number of neps in the card sliver with standard requirements.